Working Memory and Aphasia - Caspari, Isabelle; Parkinson, Stanley R.; LaPointe, Leonard L.; Katz, Richard C. (Brain and cognition, 1998)
This study investigated the relationship between working memory capacity and reading comprehension in aphasia. A measurement of working memory capacity was obtained using a modified version of Daneman and Carpenter's (1980) Reading Span Task. Sets of sentences ranging in length from one to six words were presented to 22 aphasic subjects who were required to retain the terminal words following each sentence for subsequent recognition. The maximum number of words retrieved was used as an index of working memory capacity. Two versions of the task (listening and reading) were presented depending on the subjects' ability to read. Strong positive correlations were found between working memory capacity, reading comprehension, and language function. These results support the notion that the ability of aphasic individuals to comprehend language is predictable from their working memory capacities.